Analysis of Students' Difficulties in Listening to German Audio Level B1 - Chioke, Immanuel; Hasibuan, Josua Parma; Soufyan, Ridho Abrar; Sari, Risnovita (Holistic Science, 2025)
The ability to understand audio conversations is an essential competency in learning German at the B1 level. However, many students still experience difficulties in understanding authentic conversations delivered through audio media. This study aims to analyze the factors causing these difficulties and identify their implications for the learning process. The research method used was a qualitative approach with content analysis techniques, through the administration of listening tests and the use of audio sources from digital platforms. The results showed that the main obstacles for students were the speed of native speakers' speech, limited vocabulary, dialect differences, and the lack of adequate learning media such as headsets. Furthermore, the lack of independent practice and access to German audio content also exacerbated students' inability to grasp the full context of conversations. This condition led to low student confidence and the emergence of a gap between classroom abilities and real-life communication needs. This study recommends increasing the provision of relevant audio media, teacher training in Hörverstehen learning strategies, and the habituation of intensive practice based on authentic contexts. Thus, the results of this study can serve as a basis for developing more effective learning strategies to improve German listening skills at the B1 level.